2018
DOI: 10.1038/s41398-018-0174-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between white matter integrity and serum inflammatory cytokine levels in drug-naive patients with major depressive disorder: diffusion tensor imaging study using tract-based spatial statistics

Abstract: Recently, accumulated evidence has indicated a role of inflammation in the pathogenesis of major depressive disorder (MDD). Therefore, we evaluated the relationship between white matter integrity and serum cytokine levels during the first depressive episode in drug-naive MDD patients, using a tract-based spatial statistics (TBSS) method. A total of 35 drug-naive MDD patients with a first depressive episode and 35 healthy subjects (HS) underwent diffusion tensor imaging, and an analysis was conducted using TBSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 45 publications
4
48
2
Order By: Relevance
“…that increased MD, AD, and RD in the body of the corpus callosum and inferior cerebellar peduncle were significantly correlated with current stress levels, which were also reported with the populations with high early life stress and post-traumatic stress disorders (Paul et al, 2008;O'Doherty et al, 2018). According to correlative fMRI and cytokine studies in both animals and humans (Yang et al, 2015;Benedetti et al, 2016;Sugimoto et al, 2018), these alterations might reflect elevated levels of proinflammatory cytokines, like interleukin-1α and β, tumor necrosis factor-α and interleukin-6. In summary, our correlation analyses propose that both high depression and stress levels are linked with low myelin preservation of the corpus callosum.…”
Section: Discussionmentioning
confidence: 57%
“…that increased MD, AD, and RD in the body of the corpus callosum and inferior cerebellar peduncle were significantly correlated with current stress levels, which were also reported with the populations with high early life stress and post-traumatic stress disorders (Paul et al, 2008;O'Doherty et al, 2018). According to correlative fMRI and cytokine studies in both animals and humans (Yang et al, 2015;Benedetti et al, 2016;Sugimoto et al, 2018), these alterations might reflect elevated levels of proinflammatory cytokines, like interleukin-1α and β, tumor necrosis factor-α and interleukin-6. In summary, our correlation analyses propose that both high depression and stress levels are linked with low myelin preservation of the corpus callosum.…”
Section: Discussionmentioning
confidence: 57%
“…The IFOF is involved in semantic language processing [84] but perhaps more relevant to psychiatry, connects the "salience network" to the "executive network", and therefore plays a role in integrating emotional and cognitive stimuli to facilitate goal-oriented behavior [83,85]. Reduced FA of the IFOF has been widely reported in MDD populations [86][87][88][89][90][91][92][93][94][95][96] but appears to be a non-specific finding, also being reported in bipolar disorder (BD) [89,97,98], outpatients with subsyndromal affective and psychotic symptoms [99], schizophrenia [100], Parkinson's disease with psychosis [101], and individuals with a history of childhood maltreatment [102]. Indeed, a meta-analysis of five different "emotional disorders" (MDD, BD, social anxiety disorder, obsessive-compulsive disorder, and post-traumatic stress disorder) reported reductions in FA in left IFOF (as well as other regions) compared to controls [103].…”
Section: Discussionmentioning
confidence: 99%
“…white matter is via systemic inflammation including the longterm accumulation of cytotoxic CD28 − T-cells [36]. Indeed, reduced white matter integrity (including FA of the IFOF) of both MDD [93] and BD [117] participants has been previously associated with increased serum pro-inflammatory cytokine concentrations. Negative correlations between FA and circulating inflammatory mediators have also been reported in schizophrenia [118], Alzheimer's disease [119], and healthy adults [120,121].…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine levels were measured and analyzed according to the manufacturer’s instruction. Any value that was below the limit of detection (LOD) for the cytokine assay was replaced with half of the LOD of the assay, which is following a robust and well-established method [ 24 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there is a scarce amount of research on the relationship between cytokines and WM alterations in major depression. Only one previous study showed that IL-1b was associated with reduced FA [ 24 ], but there was no difference in cytokine levels between patients with depression and normal controls. Therefore, this study aimed to investigate the difference in pro-inflammatory cytokine levels between patients with MDD and HC, and whether increased levels of pro-inflammatory cytokines influenced brain WM microstructure in MDD patients.…”
Section: Introductionmentioning
confidence: 99%